Feelings of Incompetence among Experienced Clinicians:: A Substantive Theory - Thériault, Anne; Gazzola, Nicola (European Journal for Qualitative Research in Psychotherapy, 2008)
Feelings of incompetence (FOI) are an ongoing part of the private experience of being a therapist. Although normative, they are often linked to therapist distress and to negative therapeutic processes. Yet systematic inquiries into the subjective judgment of oneself as inadequate in the role of therapist are scarce for experienced therapists. A qualitative approach was used in this study to obtain rich descriptions of experienced therapists’ encounters with feelings of incompetence. Twelve therapists with over ten years of experience were recruited for the study. They were each interviewed for ninety minutes using a semi-structured interview protocol. The resulting transcripts were analysed with procedures based on grounded theory methodology (Strauss & Corbin, 1994). A dynamic, pan-theoretical, and multidimensional theory of therapist feelings of incompetence is presented. The substantive theory describes the relationship between the four main categories of intensity of self-doubt, sources of feelings of incompetence, mediating factors, and consequences. The theory offers a structure with which to understand and diffuse this most serious hazard of our profession. It has immediate and practical relevance for psychotherapy practitioners, educators, and supervisors.